Modulation of Host Cell Signal Transduction Pathways by Helicobacter Pylori Infection - Peter JM Ceponis; Nicola L Jones (Canadian Journal of Gastroenterology)
Bacterial pathogens modulate host cell signal transduction responses to establish infection and cause disease. The purpose of the present summary, first presented at the Canadian Helicobacter Study Group meeting, is to discuss current knowledge of specific Helicobacter pylori factors, including the vacuolating cytotoxin, cytotoxin-associated gene A and the type four secretion system encoded by the cytotoxin-associated gene pathogenicity island and review the host cell signal transduction cascades that they modulate.